2011
DOI: 10.1016/j.jviscsurg.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Parastomal hernia. A study of the French federation of ostomy patients

Abstract: PSH aggravates the inherently diminished quality of life of stoma patients. There are many proposed surgical treatments but recurrence occurs in more than half of patients. Randomized trials on the treatment of PSH are nonexistent. The use of a prosthetic mesh may reduce the risk of recurrence. The prophylactic use of prophylactic mesh at the time of initial stoma formation is a strategy worthy of consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 37 publications
(38 reference statements)
10
98
2
1
Order By: Relevance
“…Our findings are concordant with others that have found increasing rates of PH after cystectomy and colorectal resections in patients with elevated BMI. While malnutrition has been reported previously as a risk factor for PH development 24 , this is the first report to our knowledge to identify a quantifiable variable, preoperative albumin level, that is significantly associated with PH development.. Like other investigators analyzing factors associated with hernia formation, we found female gender was significantly associated with PH development. 25,26 Similar to Klein and colleagues, we did not find an association between the type of stoma (end-versus Turnbull loop stoma) and the risk of developing a PH after ileal conduit.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our findings are concordant with others that have found increasing rates of PH after cystectomy and colorectal resections in patients with elevated BMI. While malnutrition has been reported previously as a risk factor for PH development 24 , this is the first report to our knowledge to identify a quantifiable variable, preoperative albumin level, that is significantly associated with PH development.. Like other investigators analyzing factors associated with hernia formation, we found female gender was significantly associated with PH development. 25,26 Similar to Klein and colleagues, we did not find an association between the type of stoma (end-versus Turnbull loop stoma) and the risk of developing a PH after ileal conduit.…”
Section: Discussionsupporting
confidence: 63%
“…Radiographic diagnosis is typically more sensitive, generally associated with higher detection rates, and may lead to a greater identification of clinically insignificant hernias. 24 The length of follow-up probably impacts the rates of PH with the lowest published PH rates seen in studies with the shortest follow-up. 8 The median follow-up for patients who did not develop a PH was 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly defined as an incisional hernia located at or immediately adjacent to a stoma, a parastomal hernia (PSH) develops in up to 78% of patients with a stoma and typically occurs within 2 years of ostomy creation but may develop as long as 20 or 30 years after surgery [7,10,11,12,13]. Goligher even went so far as to claim that some degree of parastomal herniation is inevitable given enough follow-up time [14].…”
Section: Definition and Incidencementioning
confidence: 99%
“…Patient-related risk factors for parastomal hernia include female sex; age >60 years; obesity (waist circumference of >100 cm or body mass index of >25 kg/m 2 ); smoking; comorbidities such as hypertension, chronic respiratory disease, and ascites; poor nutritional status; inlammatory bowel disease; immunosuppression; corticosteroid use; postoperative sepsis; concomitant incisional hernia; and increases in intra-abdominal pressure [8,10,11,14,15]. Surgery or technique-speciic factors that should be taken into consideration include emergency stoma placement, the type of stoma (Table 1), surgical technique for ostomy construction, the diameter of the trephine, or size of the aperture in the abdominal wall, bringing the stoma out through the resection site, placement of prophylactic mesh, and position of the stoma [2,6,7,10,16].…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…The only drawback of using ePTFE meshes is the high infection risk when it is used in a contaminated ield [2,6,39,40]. Therefore, biological prostheses have gained popularity in PSH repair because of their resistance to mesh infection in potentially contaminated areas [3,14,36]. However, it cannot be concluded that biologic meshes are preferred over synthetic prostheses for reducing the rates of short-or long-term complications [36].…”
Section: Laparoscopic Repairmentioning
confidence: 99%